APPLICATION OF CHEMICAL RIPENERS MIXTURES THE TECHNOLOGICAL QUALITY AND AGRICULTURAL PRODUCTIVITY OF SUGARCANE - Viana, Ronaldo da Silva [UNESP]; Velini, Edivaldo Domingues [UNESP]; Lisboa, Lucas Aparecido Manzani [UNESP]; Nunes Domingues Assumpcao, Ana Carolina; Monteiro Figueiredo, Paulo Alexandre [UNESP] (Univ Fed Rural Semi-arido-ufersa, 2017)
The objective of this work was to evaluate the effect of applying mixtures of chemical ripeners on the technological quality and agricultural productivity of sugarcane. The experimental design consisted of randomized blocks arranged in split-split-plots with four blocks, the main plots being constituted by sugarcane varieties SP803280 and SP801842. The subplots consisted of the application of the following products with their respective mixtures: control - absence of ripener; Sulfometrom methyl + glyphosate; ethephon + glyphosate; glyphosate and compounds of organic carboxylic radicals + glyphosate. The sub-subplots were composed of evaluation times: 0; 15 and 30 days after applying the products. Samples from each plot were collected manually and sent to the laboratory for the determination of soluble Brix solids (% broth); Sucrose content in the broth - Pol (% broth); Reducing sugars (RS%); Total reducing sugars (TRS%); Fiber (%); Purity (%); Humidity (%) and Total recoverable sugar TRS (kg t(-1)). The plots were fully harvested and the stems were taken for weighing and for characteristics determination: Yield per hectare (TCH) and Yield of sugar per hectare (TAH). The SP803280 variety was more responsive to the use of mixtures of chemical ripeners. For the technological characteristics, sulfometurom methyl (0.02 kg ha(-1)) + glyphosate (0.15 L ha(-1)) presented the best results from 15 days after application. Mixtures of chemical ripeners did not increase the yields of stalks and sugar per area.
Keywords: Phytoregulators; Ripening; Saccharum spp